Pengaruh Likuiditas, Profitabilitas dan Audit Tenure Terhadap Opini Audit Going Concern Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Simatupang, Riqqah Hasanah; Listiorini, Listiorini (Graha Mitra Edukasi, 2023)
This study aims to determine the effect of liquidity, profitability, solvency and audit tenure on going concern audit opinions with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The type of research used in this research is associative with a quantitative approach method. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period which amounted by 181 companies, the sampling method used was purposive sample, with a total sample of 100 companies. The data analysis technique used is logistic regression analysis with statistical data processing using SPSS version 20.0 data processing application. The results of this study indicate that liquidity, profitability and audit tenure have no effect on going concern audit opinions. Firm size is able to moderate the relationship between the influence of liquidity on going concern audit opinions, but firm size is not able to moderate the relationship between the effect of profitability, audit tenure on going concern audit opinions on manufacturing companies listed on the Indonesia Stock Exchange (IDX).